Overview about GIS multi-criteria spatial analysis for micro hydropower plant site suitability in South Ogan Komering Ulu District, South Sumatera, Indonesia - Wawan Hendriawan Nur; Yuliana Yuliana; Yuliana Susilowati; Yugo Kumoro; Yunarto Yunarto (Bulletin of Electrical Engineering and Informatics, 2021)
Morphology in South OKU District is the potential of a micro hydropower plant (MHPP) as an alternative power source. This potential has not been fully utilized, although many un-electrified villages are in several remote areas. Identification planning for MHPP is one of the most critical planning tasks and requires excellent multi-criteria spatial analysis. GIS and multi-criteria analysis have played an essential role in analyzing suitable locations for MHPP development. GIS and multi-criteria spatial analysis consist of detailed investigations of ongoing sites and suitability for specific planning. This research aims to overview GIS multi-criteria spatial analysis for MHPP site suitability based on electricity South OKU demands. The most critical data and criteria to decide the best site suitability are un-electrified villages, rivers, land use, slope, landslide vulnerability, and elevation. All of the data were generated into the raster data format. Quantitative modeling used AHP as a multi-criteria analysis method, and a weighted score is determined by considering the comparison of each criterion. Finally, the criterion layer was calculated by open-source QGIS to create a site suitability map. The field study verified the resulting map, and there is a match between the preferred locations and the field survey. The research results preferred Sungai Are, Sindang Danau, and Kisam Tinggi Sub-district as the best suitability for MHPP development.